Atomic structure and chemistry of dislocation cores at low-angle tilt grain boundary in SrTiO3 bicrystals. (1st May 2015) - Du, Hongchu; Jia, Chun-Lin; Houben, Lothar; Metlenko, Veronika; De Souza, Roger A.; Waser, Rainer; Mayer, Joachim
Graphical abstract: Abstract: Dislocations in perovskite oxides have been found to have important impacts on their electronic and ionic transportation properties, which are believed to be related to the structure and chemistry of dislocation cores. For dislocation cores at a 6° low-angle [0 0 1] tilt grain boundary in SrTiO3, an embedded TiOx rocksalt-like structure has been suggested, consistent with a deficiency of Sr. However, direct evidence supporting these suggestions has not been obtained up to now. In this work, we reveal the atomic structure and chemistry of edge dislocation cores at a low-angle [0 0 1] symmetric tilt-boundary in SrTiO3 bicrystals by imaging techniques of high-angle annular dark-field scanning transmission electron microscopy (HAADF-STEM) and electron energy loss spectroscopy (EELS) with an FEI Titan cube 3 60–300 (PICO) microscope operated at 80 kV. The experimental results demonstrate direct evidence for a local coordination of edge-sharing TiO6 octahedra at the dislocation cores, which can be understood as the result of strain. The local coordination of edge-sharing TiO6 octahedra is associated with the face-centered cubic (FCC) NaCl-type TiO phase. The present study therefore provides a solid structural and chemical basis for understanding the properties of dislocations.